ISOLATION, STRUCTURE ELUCIDATION & ANTIDIABETIC POTENTIAL OF ROSA BRUNONII L. FRUIT – FIGHT DIABETES WITH NATURAL REMEDIES - Ejaz Ahmad; Muhammad Jahangeer; Nadeem Irfan Bukhari; Abid Sarwar; Tariq Aziz; Metab Alharbi; Abdulrahman Alshammari; Abdullah F. Alasmari; Abid Sarwar (Journal of the Chilean Chemical Society, 2023)
Diabetes mellitus (DM) is a metabolic disorder that is marked by high blood glucose levels. Members of the Rosaceae family are a good source of antioxidants. Therefore, the current work sought to examine the potential for in-vitro alpha-amylase and alpha-glucosidase inhibition and the antidiabetic activity of Rosa brunonii L. fruit chloroform extract (RBFCE) against Alloxan (ALXN) induced diabetes in rats. RBFCE concentrations ranging from 20, 50, 100, 250, 500, and 750 g/mL were used in in-vitro activities, while oral doses of 500 mg/kg, 750 mg/kg, and 1000 mg/kg were given to rats in an in-vivo trial for 21 days. Isolation was carried out through column chromatography and modern spectroscopic techniques were used for characterization and structure elucidation. The isolated compound was identified as catechin. For alpha-amylase and alpha-glucosidase inhibition activity, RBFCE had IC50 values of 322.06±17.40 and 248.93±1.62, respectively. The IC50 values for acarbose against alpha-amylase and alpha-glucosidase inhibition were 64.64±3.70 and 67.60±4.20, respectively. RBFCE treatment regulated blood glucose levels dose-dependently over a 21-day study period. Histopathological studies revealed that RBFCE has recovered the damaged acinar structures to some extent in pancreatic tissue. Only focal tissue destruction observed. RBFCE treatment displayed normal glomeruli with no signs of inflammation, proliferation, necrosis, cipher of thyroidization and fibrosis. All the extract-treated groups had more protected pancreatic and kidney tissue than control group in dose-dependent manner. The current study results revealed that RBFCE had prominent alpha-amylase and alpha-glucosidase inhibition activity, regulates blood glucose level and normalize histopathological markers in diabetic rats compared to the negative control group.